HISTORY LEARNING PROCESS AT STATE SMA NEGERI 1 KABILA - Arkani, Rugaiya; Mohamad, Sutrisno; Arrazaq, Naufal Raffi (CV. Fahr Publishing, 2025)
This study aims to determine how the history learning process is carried out at Kabila 1 Public High School. This study applies a qualitative method with a descriptive approach that describes the history learning process at Kabila 1 Public High School. Data collection in this study was conducted through interviews with history teachers and students regarding the history learning process at SMA Negeri 1 Kabila. Observation was carried out by observing the activities that took place between teachers and students in class XI-3, which had 31 students and 1 history teacher, during the history learning process and documentation. The results of this study show that the history learning process at SMA Negeri 1 Kabila is effective, and most students show positive responses to the material taught, although some students are less focused. However, conducting history lessons in the afternoon is one of the challenges faced by teachers and students during the learning process in the classroom.